2008
DOI: 10.1159/000139459
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Olfactory Lobe of Decapod Crustaceans

Abstract: Studies on the crustacean nervous system have been responsible for advances in neuroscience and continue to play an important role in comparative neurobiology. The organization of crustacean brains provides clues about their phylogeny and might also offer some hints regarding their lifestyles. In this study, we compared the organization of specific brain regions of three species of marine shrimp with two species of freshwater prawns, making possible the identification of a pathway issuing from the periphery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Immunohistochemistry revealing CaMKII showed intense labeling of a bundle of fibers within the protocerebral bridge, central body, and protocerebral tracts in the anterior medial protocerebrum and in the posterior medial protocerebrum. In the deutocerebrum, an intense CaMKII immunoreaction was observed in the olfactory-globular tract (OGT) and in the prospective deutocerebral commissure, as also observed by [19] (Figure 2B). The immune reaction using the FMRFamide antibody showed labeled cells in the cell clusters 6, 8, 9, and 11.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Immunohistochemistry revealing CaMKII showed intense labeling of a bundle of fibers within the protocerebral bridge, central body, and protocerebral tracts in the anterior medial protocerebrum and in the posterior medial protocerebrum. In the deutocerebrum, an intense CaMKII immunoreaction was observed in the olfactory-globular tract (OGT) and in the prospective deutocerebral commissure, as also observed by [19] (Figure 2B). The immune reaction using the FMRFamide antibody showed labeled cells in the cell clusters 6, 8, 9, and 11.…”
Section: Resultssupporting
confidence: 61%
“…In general, the visual sensory stimuli are converted into motor responses and eventually translated into behaviors [38]. In a previous report, we demonstrated in freshwater prawns and marine shrimps that the OL is responsible for converting sensory stimuli into motor information [19]. Here, we showed that CaMKII is expressed in the same sites as FMRFamide (which was previously used to control for the labeling of neuronal elements in crustaceans [24], [25]) and one postsynaptic glutamate receptor in the sensory structures.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The two arms of OGTs touch each other medially forming a characteristic chiasma located next to the central body (Fanenbruck et al, 2004). However, the caudal-rostral organization of the median protocerebrum into the anterior median and posterior median protocerebral neuropiles is still discernible (Ammar et al, 2008). The protocerebral bridge and the central body are clearly delineated, as are the paired OLs, the lateral antennule neuropil and the median antennule neuropil (Ammar et al, 2008).…”
Section: Nervous Systemmentioning
confidence: 99%